High-Resolution 3D Heart Models of Cardiomyocyte Subpopulations in Cleared Murine Heart - Ren, Huiying; Pu, Zhaoli; Sun, Tianyi; Chen, Tangting; Liu, Leiying; Liu, Zhu; O’Shea, Christopher; Pavlovic, Davor; Tan, Xiaoqiu; Lei, Ming (Frontiers in Physiology, 2022)
Biological tissues are naturally three-dimensional (3-D) opaque structures, which poses a major challenge for deep imaging of spatial distribution and localization of specific cell types in organs in biomedical research. Here we present a 3-D heart imaging reconstruction approach by combining an improved heart tissue-clearing technique with high-resolution light-sheet fluorescence microscopy (LSFM). We have conducted three-dimensional and multi-scale volumetric imaging of ultra-thin planes of murine hearts for up to 2,000 images per heart in x-, y- and z three directions. High-resolution 3-D volume heart models were constructed in real-time by the Zeiss Zen programme. By using such approach, we investigated detailed three-dimensional spatial distributions of two specific cardiomyocyte populations including HCN4 expressing pacemaker cells and Pnmt+ cell-derived cardiomyocytes by using reporter mouse lines Hcn4DreER/tdTomato and PnmtCre/ChR2-tdTomato. HCN4 is distributed throughout right atrial nodal regions (i.e. sinoatrial and atrioventricular nodes) and the superior-inferior vena cava axis, while Pnmt+ cell derived cardiomyocytes show distinct ventral, left heart and dorsal side distribution pattern. Our further electrophysiological analysis indicates that Pnmt+cell-derived cardiomyocytes rich left ventricular (LV) base has higher susceptible to ventricular arrhythmia under adrenergic stress than LV apex, right ventricle regions. Thus our 3-D heart imaging reconstruction approach provides a new solution for studying geometrical, topological and physiological characteristics of specific cell types in organs.